Some folk medicinal plants of Bhiravakona hills of Prakasam district, A. P., India - Venkata Rami Reddy, K; Nagalakshmi Devamma, M; Prayaga Murty, P (Current Botany, 2013)
Mankind has blessed with variety of natural products which help us in day to day life. These extraordinary substances help us to treat different ailments of human beings and other pet animals. In the recent years ethnopharmaocology played a vital role in the undeveloped and developing countries of the Globe. The present communication deals with the plants used to treat different ailments of local people of Bhiravakona hills of Andhra Pradesh, India. 153 plant species have been identified for 19 different ailments. plants used for each ailment are Abortion (7), Acidity (9),Asthama (8), Cold (7), Cough (8), Diabetes (15), Diarrhoea (17), Dysentery (31), Fever(29),Fractures (9), Head ache (8), Jaundice (15), Kidney Stones (3), Malaria fever (3), Piles (11), Sexual disease (1), Skin disease (22), Stomachache (14) and Ulcers. Depending upon the plant part used, root constitutes the highest percentage (30.72%) of utilization and wood, latex; inflorescence and corm the lowest (0.65%).There is an urgent need for follow-up ethnopharmacological screening based on local people claims and beliefs and formulate and standardize some herbal medicines based on ethnotherapeutics either with single plant or in combination for their safe and sustained use for human welfare.